Pengaruh Stres Kerja dan Beban Kerja terhadap Kinerja Karyawan Puskesmas Mijen Semarang - Yunnan Afgani; Euis Soliha (IPM2KPE, 2024)
This research aims to determine and analyze the influence of work stress and workload on employee performance at the Mijen Semarang Community Health Center partially and simultaneously. The location of this research is the Mijen Semarang Community Health Center. The research sample consisted of seventy-two people according to the total number of employees at the Mijen Semarang Community Health Center using the census method. The analysis in this research uses multiple regression analysis, f test, t test and coefficient of determination. Based on multiple regression analysis, it shows that work stress has a significant negative influence on employee performance. The higher the work stress, the lower the employee's performance. Workload has a significant negative influence on employee performance. The higher the workload, the lower the employee's performance. The results of the f test show that the work stress and workload variables simultaneously influence employee performance. The t test results show that the test results are in accordance with the proposed hypothesis and can be accepted. The coefficient of determination shows the magnitude of the influence of work stress and workload on employee performance. Keywords: Workload, Employee Performance, Work Stress